SELF-EXPRESSION AND IDENTITY NEGOTIATION IN GRADUATION PHOTOGRAPHS ON INSTAGRAM - Moh Rochim Alamsa; Mohammad Isa Pramana Koesoemadinata; Riksa Belasunda (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This article examines graduation photographs on Instagram as a contemporary visual practice that reflects a shift in the meaning of graduation. Employing a descriptive qualitative method grounded in Roland Barthes’ semiotic approach at the level of connotation encompassing trick effects, pose, objects, photogenia, and Aestheticism. This study analyzes expressive graduation photographs by drawing visual data from three Indonesian cities with the highest student populations: Jakarta, Bandung, and Yogyakarta. The findings indicate that graduation photographs on Instagram not only represent academic achievement but also function as a medium of self-expression and identity negotiation across personal, relational, and cultural dimensions. The analysis further reveals that graduation is interpreted as a multifaceted transitional event in which institutional symbols coexist with personal and context specific self-narratives. This article contributes to visual and cultural studies by demonstrating how graduation is re-signified as a plural transitional practice, where institutional legitimacy is articulated alongside personal and contextual narratives through photographic representation.